Identification of Legal Protection on Covid-19 Vaccine Services to the Public During the Pandemic Crisis in Indonesia: Legal Health Study - Gunawan Widjaja (IHSA Institute, 2022)
This study examines the identification of legal protection for recipients of the COVID vaccine during the pandemic crisis in Indonesia, which is viewed from the point of view of the study of the health law. We believe that the Government certainly has some supporters and protectors in carrying out its policies, namely vaccination services for citizens. To discuss this topic, we are supported by some scientific publications, especially findings on vaccination studies in the context of legal protection for vaccine recipients and the legal basis for state action in implementing policies. We found data from various study sources from legal and health scientific journal publications, especially vaccination conflicts, both from international and domestic journals. In order to make it easier for us to take essential points as the findings of this study, first, we have listed them under the phenomenological approach, which is a method or method that we do to obtain information, then we examine them to get the gist of the relevant answers. Based on the data exposure and discussion, we found that in carrying out the vaccination program, the Government first has a responsibility, namely to ensure that its citizens are healthy and prosperous so that based on this obligation, the Government makes a policy. Then the Government also coordinates with health parties in the field and the community irregularities in its implementation. The Government is considered unable to carry out vaccinations as mandated by this policy because people still need awareness and belief to run optimally.